THE EFFECT OF RADEC LEARNING MODEL ON STUDENTS’ SELF-EFFICACY IN ELEMENTARY SCHOOLS IN CIREBON CITY - Yuli Yani; Arifuddin, Ahmad; Andini, Wulan; Rohman, Khabibur (AULADUNA: Jurnal Pendidikan Dasar Islam, 2025)
The purpose of this study was to examine the effect of the RADEC (Read, Answer, Discuss, Explain, and Create) learning model on students’ self-efficacy. This study used an experimental method with a pretest-posttest control group design. The population in this study consisted of fifth-grade students at SDN Sekecamatan Kesambi, Cirebon City, which holds an A accreditation. The sample consisted of 21 students from SDN Mega Eltra, the experimental group, and 26 students from SDN Karya Winaya, the control group. Data were collected using a self-efficacy questionnaire. Statistical tests included normality, homogeneity, the Mann-Whitney U test, and the N-Gain test. The analysis results showed moderate N-gain scores in the experimental group and low N-gain scores in the control group. This analysis suggests that the implementation of the RADEC learning model has a more significant impact on improving students’ self-efficacy compared to the conventional image-assisted learning model, even after accounting for the initial score differences between the two groups.